DIFFERENTIATION T LYMPHOCYTE CELLS EXPRESSING INTERLEUKIN-17 PERCENTAGE ON HEALTHY PERSON AND ADULT ACUTE MYELOID LEUKEMIA PATIENT - Elvan Dwi Widyadi; Yetti Hernaningsih; Endang Retnowati; Ugroseno Ugroseno; Ryzky Widi Atmaja (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
Acute Mieloid Leukemia (AML) is a hematologic cause of cancer deaths of 1.2% including a relatively rare disease but by the end of the decade there is an increase in the number of new cases. The immune system in AML is caused by gene mutations giving immunosuppressive effects so that the immune system will be inhibited in eliminating leukemia cells. The immune response of tumors is important to determine the prognosis, development of new cancer immunotherapy as well. One of the subset of lymphocytes T is gdT lymphocyte cell with innate nature, but until now no information is required about gdT cell profile in AML patients. gdT cells have properties as antitumors played by Interferon production g (INF g), and the nature of protumor by interleukin 17 (IL-17). The percentage of lymphocyte T (CD3 +) of AML patients and healthy people did not differ (p = 0.528), indicating, not being activated for proliferation. gdT Lymphocyte cells percentage in healthy people by race, genetic and exposure to the surrounding environment such as infection. Percentage of gdT lymphocyte of AML patients and healthy people was not different from (p = 0.694), showed an immune response by gdT cells Unefected to proliferate. The percentage of gdT llimfocytes expressing the interleukin 17 (gdT17 cells)in patients AML and healthy people did not differ significantly (p = 0.436), this indicates inhibited proliferation.